2013
DOI: 10.1249/mss.0b013e31827f0d9c
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Activity and Sedentary Behavior from an Accelerometer on the Hip or Wrist

Abstract: Previously the National Health and Examination Survey measured physical activity with an accelerometer worn on the hip for seven days, but recently changed the location of the monitor to the wrist. PURPOSE This study compared estimates of physical activity intensity and type with an accelerometer on the hip versus the wrist. METHODS Healthy adults (n=37) wore triaxial accelerometers (Wockets) on the hip and dominant wrist along with a portable metabolic unit to measure energy expenditure during 20 activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(172 citation statements)
references
References 43 publications
4
166
0
2
Order By: Relevance
“…Participants have traditionally worn accelerometers on a belt around their waist during waking hours and remove them for water-based activities, a methodology and protocol that has been shown to be both valid and reliable. 23,24 Wearing a device on a wrist or ankle can be helpful in quantifying behaviors that have different positions 25,26 and can be less burdensome than using a waist-worn device. The movement detected by accelerometers is converted to electrical signals or "counts" that can be summed over a period of time to quantify total sedentary time (minutes) or patterns of sedentary time (eg, duration of bouts or episodes, breaks in sedentary time).…”
mentioning
confidence: 99%
“…Participants have traditionally worn accelerometers on a belt around their waist during waking hours and remove them for water-based activities, a methodology and protocol that has been shown to be both valid and reliable. 23,24 Wearing a device on a wrist or ankle can be helpful in quantifying behaviors that have different positions 25,26 and can be less burdensome than using a waist-worn device. The movement detected by accelerometers is converted to electrical signals or "counts" that can be summed over a period of time to quantify total sedentary time (minutes) or patterns of sedentary time (eg, duration of bouts or episodes, breaks in sedentary time).…”
mentioning
confidence: 99%
“…We applied previously established methods to process raw accelerometer sensor data to determine sedentary behavior and physical activity. [16] Initially, raw data was converted to a motion summary count using an area under the curve calculation after removing the effects of gravity, which provided activity counts per minute. Thresholds for sedentary behavior (<50.92 counts/minute) and moderate-vigorous physical activity (>305.36 counts/minute) were used from a validation study of Android devices.…”
Section: Resultsmentioning
confidence: 99%
“…97 In this study, we suggested to participants that they wear the accelerometer around their waist rather than around their wrist, because wrist-worn accelerometers are not as accurate as hip-worn accelerometers at classifying activity and sedentary behaviour. 196 However, the interviews suggest that wearing the accelerometer in this way was a burden for some participants, especially for those with abdominal wound problems or a stoma. Thus, for the purposes of consistency in measuring the amount of physical activity, all people with CRC should be requested to wear the device on the wrist in future studies.…”
Section: Phase 2 Qualitative Studymentioning
confidence: 99%